Opportunities to Reduce Overuse of Antibiotics for Perinatal Group B Streptococcal Disease Prevention and Management of Preterm Premature Rupture of Membranes - Nina E. Glass; Jay Schulkin; Shadi Chamany; Laura E. Riley; Anne Schuchat; Stephanie Schrag (Hindawi Limited, 2005)
Objective: To identify opportunities to reduce overuse of antibiotics for prevention of perinatal group B streptococcal (GBS) disease and management of preterm premature rupture of membranes (pPROM).